Refractory inflammatory hydrocephalus: A case report of a rare and complicated delayed sequelae following cerebral hemispherectomy surgery for epilepsy - Akshay Sharma; Efstathios Kondylis; Shaarada Srivatsa; Nehaw Sarmey; Deepak Lachhwani; Laura Nedorezov; William Bingaman (Epilepsy & Behavior Reports, 2024)
Hydrocephalus is a known complication following surgical resection of a cerebral hemisphere for refractory epilepsy, yet the pathological mechanism remains poorly understood. We present a case of refractory aseptic inflammatory hydrocephalus following cerebral hemispherectomy surgery for refractory epilepsy treated with a combination of cerebral spinal fluid (CSF) diversion and immunosuppression via IL-1 receptor agonist, Anakinra. At 6 month follow up, the patient had returned to neurologic baseline, with improvement in school and physical therapy performance. Further investigation into the beneficial role of immunosuppressive therapy is needed to better understand the relationship between neuro-inflammation and improving outcomes following epilepsy surgery.